Therapeutic apheresis during pregnancy: A single center experience. (October 2019) - Colpo, Anna; Marson, Piero; Pavanello, Francesca; Tison, Tiziana; Gervasi, Maria Teresa; Zambon, Alessandra; Ruffatti, Amelia; De Silvestro, Giustina; Hoxha, Ariela
Abstract: Introduction: Therapeutic apheresis (TA) represents a treatment option for pre-existing conditions or diseases occurring during gestation. Although pregnancy is not a contraindication per se, due to the lack of evidence-based guidelines and presumed risk of maternal/fetal adverse events there is a general resistance to its application. Material and methods: Between January 2005 and August 2017, at the Apheresis Unit of the University Hospital of Padua 936 TA procedures were performed during 57 pregnancies in 48 patients: 813 Plasma Exchange sessions, 119 Immunoadsorptions, 4 Red Blood Cell exchanges. The treated disease were as follows: antiphospholipid syndrome (18 patients), autoimmune congenital heart block (18), myasthenia gravis (3), Rh alloimmunization (2), systemic sclerosis (1), suspected autoimmune encephalitis (1), severe hypertriglyceridaemia (1), post partum hemolytic-uremic syndrome (1), sickle cell disease (1), lupus nephritis (1) and thrombotic thrombocytopenic purpura (1). Results: In the time period considered the apheresis sessions applied to pregnant women were 7.1% of the total (n = 13.251). The median age at the first treatment was 33 years. The median week of gestation (WG) at the beginning of treatments was 21. Twenty (2.1%) sessions were complicated by adverse events, none requiring or prolonging hospitalization. There were 50 live births, 5 spontaneous abortions and 2 voluntary terminations of pregnancy. Median WG at delivery was 35 and caesarean section was performed in 46 cases. Conclusions: Our data showed that TA in pregnancy is well tolerated. Close collaboration between clinician, obstetrician and TA specialist is crucial to ensure a good outcome of high-risk pregnancies.